Intimidade performada: A gestão da visibilidade em "Memórias , crônicas e declarações de amor", de Marisa Monte - Rusvel Nantes Dornelas Amaro (2011)
In April 2007, the Brazilian edition of Rolling Stone magazine arrived at the newsstand with the at least curious headlines: who is afraid of Marisa Monte?. Taking in consideration the autonomy conquered by the artist in relation to the phonographic market and the increasing investment in the construction of the own image, this research discusses the reconfiguration of the visibility from certain unlimit between the domains of the public and the private. For this, we analyzed photographs made by Marisa Monte for the graphical project of the record and songbook Memórias, crônicas e declarações de amor (Memories, chronicles and declaration of love - 2000). Consideringthat the mediatic products are even more permeated by autobiographical narratives, we search to verify some traces that structure the contemporary subjectivity, in a context of emergency of theordinary life and the common man. We also searched to understand how the celebrization processes had been transformed due to a constant exteriorization of the privacy. Through the analysis of the images, we desired to reflect about a sociocultural dynamics that intensified the demand of observation of the other and, at the same time, legitimized the exposition and the management of herself. Therefore, when we contextualized the position of Marisa Monte in relation to the Braziliancultural industry, we tried to measure authorial traces that make her proper music part of a strategy of maintenance of the fame, answering, thus, to the contemporary practices that stimulate the cult of the performance.